Rational and Meta-Rational Decision Model for Organizational Management. Transdisciplinary Exploratory Approach to Problem Solving in Scientific Management - Acevedo Borrego, Adolfo Oswaldo (2023)
In academy, which includes scientific management or industrial engineering, decisions in organizations and the techniques used are fully based on rational criteria, including various techniques derived from learning from experience, called intuitive or heuristic. Academia does not consider approaches that are not framed within the rational criteria, since it considers that they do not exist or are irrelevant. The objective of the study is to develop a different approach to decision making under a transdisciplinary perspective and through the design of a conceptual model of decisions that considers the range of rational and meta-rational decisions in all organizational scenarios where problems are solved. It has been found that professionals define the decision criteria according to the perceived scenario: if it is simple and concrete, the technique is systematic and focused; if it is undefined or amorphous, the technique is soft with options; if the problem is complex, emotional criteria, beliefs and atavisms are considered, or creative and heuristic options are invented. The transdisciplinary perspective allows the inclusion of criteria and methods of problem solving not considered by academia, which enriches the praxis of the profession in the management of organizations.